The Effect of Managerial Ability on Risk Reporting in Indonesia: Evidence for Energy and Palm Oil Companies - Zairin Gentiga Muhammad; Khairunnisa Hera; Respati Dwi Kismayanti; Putri Nur Afni Camelia; Sang Lim Thien; Ulupui I Gusti Ketut Agung (Studies in Business and Economics)
Risk reporting is a critical aspect of risk management for energy and palm oil companies as they address complex industry challenges. This article examines the influence of management ability on risk reporting in both industries. The results show that managerial ability has an impact on credit risk assessment, risk behavior, financial reporting, timeliness, stock price crash risk, and tax results. Management’s discretionary disclosure behavior allows it to exercise subjectivity in determining both the content and manner of disclosure. This research identifies a risk reporting factor associated with competent managers that indicates their desire to disclose risk-related information in annual reports in highly competitive markets. This work complements previous research on competent managers in competitive markets and provides valuable insights into the risk reporting practices of highly skilled managers in such environments.